E-Internship Management Model for Islamic Development Bank in Saudi Arabia - Abdulkadir, Abdullah Abduljabar (2011)
A key factor which makes Web Based Applications (WBA) highly recommended over stand alone system is centralized mechanism used in those applications. Internship Management in Islamic Development Bank (IDB) use variety of systems which are mostly mixture of WBA and some manual procedures. This study would try to enhanced the process of the current management procedures by converting it entirely into a WBA which solved some of the critical issues which were not supported by the current system. The proposed system adopted Extreme Programming (XP) and Rational Unified Process (RUP) methodology in order to fulfill its objectives.